Femoral head diameters in Nepalese patients undergoing hemiarthroplasty - Gupta, Manoj P.; Chaurasia, Lokraj; Jha, Sanjeet Kumar (International Journal of Research in Orthopaedics, 2021)
Background: Sizing of the femoral head is important for determining the appropriate size of implants to be used for a patient undergoing hip arthroplasty. The present study aimed to determine the mean diameter of femoral head in Nepalese population who underwent hemiarthroplasty in our department. Methods: We retrospectively reviewed the medical records of patients who underwent hemiarthroplasty from December 2016 till December 2020. We included patients aged more than 50 years who underwent hemiarthroplasty. The diameter of the femoral head was measured intraoperatively using standard fully circular templates. For radiological measurements, X-ray of pelvis with hips anteroposterior view were included. Results: A total of 600 femoral heads were evaluated, 400 of women and 200 of men. Of these cases, the femoral head diameter were evaluated based on x-ray pelvis in 500 cases and rest of the 100 cases were evaluated intraoperatively. The mean age of the patients in our sample was 75.2±9.4 (range 50–90) years. Overall, the mean femoral head diameter (with intact articular cartilage) was 44.9±3.2 (range 39–53 mm) mm. Among the male patients, mean femoral head diameter was 47.7±2.8 mm, which was found to be significantly higher than that of female patients, who had a mean femoral head diameter of 43.7±2.4 mm, p value <0.05. Conclusions: Further studies are needed in other geographical locations, so that reference values could be established for specific regions.